High-quality-factor transition metal element doped garnet-structured aluminate scintillating material as well as preparation method and application thereof
Patent Information
- Application Number
- JP2024087461
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-21
- Filing Date
- 2024-05-29
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2044-05-29
AI Technical Summary
【0021】 1、本発明では、イオン半径及び電気陰性度がAl3+と類似した遷移金属元素がドープされるガーネット構造アルミン酸塩シンチレーション材料の技術的方案が提案され、合理的な予測実験的検証に基づいて適切なドープイオンを選別する。 2、本発明では、ガーネット構造アルミン酸塩シンチレーション材料に遷移金属元素がドープされた後、材料の発光性能が大幅に改善され、シンチレーション性能に関連する品質係数(光収率/シンチレーション減衰時間)が大幅に向上されること、シンチレーションの上昇時間又は減衰時間が短縮されること、及び残光レベルが大幅に減少することを含むがこれに限定されない。 3、本発明では、遷移金属元素がガーネット構造アルミン酸塩シンチレーション材料にドープされることによって得られる高品質係数を持つシンチレーション材料は、高エネルギー物理学、宇宙空間物理、工業用非破壊検査、安全監査、鉱物と油井の探査、核医学イメージング(X-CT、TOF-PET)においてよりよく応用することができる。
Smart Images

Figure 2025029569000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention uses Al as the ionic radius and electronegativity. 3+ This invention relates to a garnet-structure aluminate scintillation material with high quality factor obtained by doping with transition metal elements similar to those described above, and its manufacturing method and application, which belong to the field of scintillation material technology. [Background technology]
[0002] Inorganic scintillation materials are energy converters that can convert the energy of high-energy radiation (X-rays, gamma rays) or particles (protons, neutrons, etc.) into ultraviolet or visible light. By combining it with a subsequent photoelectric conversion element (photodiode, silicon photomultiplier tube, photomultiplier tube, etc.), it can realize effective detection of radiation. X-rays or gamma rays generated by a radiation source enter a scintillator, the radiation is absorbed by the scintillator to generate scintillation light, and the light signal is converted into an electrical signal by a photodetector, which collects, stores and displays the electrical signal, thereby realizing accurate measurement of many physical parameters such as energy, momentum, direction and duration of these invisible high-energy radiation or particles. At present, detectors made from inorganic scintillation crystals are widely applied in many fields such as high-energy physics, space physics, industrial non-destructive testing, safety auditing, mineral and oil well exploration, nuclear medicine imaging (X-CT, TOF-PET), etc., and are the mainstream of scintillation material development and have huge market potential.
[0003] With the rapid development of nuclear exploration and related technologies, higher requirements are put forward for the performance of scintillation crystals, and the traditional NaI:Tl, CsI:Tl, Bi4Ge3O 12Scintillation crystals such as (BGO), BaF2, and PbWO4 (PWO) are no longer able to meet the requirements for use, and the goal we have been striving for is to develop a scintillation crystal with high density, large atomic number, high light output, fast decay, and radiation resistance. The next-generation garnet-structured aluminate scintillation crystal has gradually become the focus of research due to its characteristics such as high light output, excellent energy resolution, and fast decay.
[0004] Rare-earth doped garnet structure aluminates can be considered as a distorted dodecahedron in which regular tetrahedrons and regular octahedrons are spatially interconnected through oxygen ions at the apex angles, and the voids formed are distorted dodecahedrons. One unit has eight stoichiometric units, [A 3+ ]3[B 3+ ]2[Y 3+ ]3O 12 There is a molecule of Y 3+ is in a tetrahedron of four oxygen ions, and B 3+ is in an octahedron of six oxygen ions, and A 3+ is located in a distorted dodecahedron formed by the gaps between a regular tetrahedron and a regular octahedron. Ce 3+ When doped with some trivalent rare earth ions such as Ce, they generally enter the dodecahedral sites. 3+ Doped Gadolinium Aluminum Gallium Scintillation Crystal (Gd3Al2Ga3O 12 :Ce, GAGG:Ce) is a rare earth ion that has been developed in recent years under the guidance of "band gap engineering". 3+ is used as an activator, and Ce 3+ It uses the 5d → 4f parity allowed transition of 1d to 4f to obtain fast decay emission. This crystal has the characteristics of high light output, fast emission decay, large effective atomic number, high density, no self-radiation, non-deliquescent, etc., excellent comprehensive performance, and has great prospects for development. With the further development of PET technology, the introduction of time-of-flight (TOF) technology has been proposed to improve its imaging resolution, reduce the patient dose, and shorten the scan time. However, TOF technology requires the scintillator to have a faster decay time and higher light yield corresponding to higher image resolution and positioning accuracy.
[0005] The fast component of the scintillation decay time of the GAGG:Ce crystal is about 90 ns, whereas the conventional bismuth germanate (Bi4Ge3O 12 Although the decay time is significantly faster than that of GAGG:Ce (abbreviated as BGO), a shorter scintillation decay time is required for practical applications to better exert its advantages. In order to accelerate the scintillation decay rate of GAGG:Ce crystals, Patent Document 1 discloses a method of doping rare earth lattice sites and adjusting the Al-Ga ratio to improve GAGG scintillation and optical performance. In addition to adjusting the substrate components, co-doping with ions is also the most common means to adjust the scintillation performance. Wu et al. 2+ Co-doped with Ce and partially doped with Ce through a charge balancing mechanism. 3 Ce emits light faster 4+ converted to Mg, thereby shortening the scintillation decay time of GAGG:Ce crystals, but the light yield and energy resolution were somewhat reduced (Non-Patent Document 1). 2+ Co-doping can significantly shorten the decay time, and the effect is Ca 2+ reported that the scintillation response time is superior to co-doping (Non-Patent Document 2). The method of shortening the scintillation response time disclosed in Patent Document 2 is co-doping rare earth lattice sites, and the effect of co-doping ions on the Al site on the time is not considered. Patent Document 3 discloses gadolinium aluminum gallium tyrration materials improved by doping octahedral lattice sites and their manufacturing methods and applications, and discloses that at least one of hafnium Hf, zirconium Zr, copper Cu, zinc Zn, tin Sn, lead Pb, titanium Ti, tellurium Te, and terbium Tb is co-doped on the Al site, but this mainly depends on the change in the spatial structure, and Gd 3+ and Al 3+ By co-doping with elements with ionic radii between 0.01 and 0.1, they are preferentially distributed in the octahedral lattice sites around the luminescent center Ce, suppressing the formation of antisite defects and thereby accelerating the decay. 3+ It does not consider whether it will affect Ce4+ The presence of ions was not taken into consideration. After co-doping with the above ions, the quality factor was slightly improved, but the improvement effect was not obvious. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2014 / 171985 [Patent Document 2] International Publication No. 2017 / 059832 [Patent Document 3] China Patent Application Publication No. 115322784 [Non-patent literature]
[0007] [Non-Patent Document 1] Yuntao Wu, Fang Meng, Qi Li, Merry Koschan, and Charles L. Melcher, "Role of Ce4+ in the Scintillation Mechanism of Codoped Gd3Ga3Al2O12:Ce", PHYSICAL REVIEW APPLIED 2, 044009 (2014), [Non-Patent Document 2] Kei Kamada, Martin Nikl, Shunsuke Kurosawa, Alena Beitlerova, Aya Nagura, Yasuhiro Shoji, "Alkali earth co-doping effects on luminescence and scintillation properties of Ce doped Gd3Al2Ga3O12 scintillator", Optical Materials 41 (2015) 63-66 Summary of the Invention [Problem to be solved by the invention]
[0008] In order to achieve the practical needs and the above-mentioned objects, the object of the present invention is to provide a method for producing a fluorine-containing ... 3+ Similar to the nucleus, the electron configuration is [Ar]3d n 4s 1 ~ 2 The present invention provides a garnet-structured aluminate scintillation material doped with a transition metal element (n≧5), and a method for producing the same and applications thereof. [Means for solving the problem]
[0009] In one aspect, the present invention provides a transition metal element-doped garnet-structure aluminate scintillation material, the chemical formula of the transition metal element-doped garnet-structure aluminate scintillation material is RE 3-x-a Ce x A a Al 5-y-z D y M z O 12 where x is 0 <x≦0.15、yは0≦y≦3、zは0<z≦0.1、aは0≦a≦0.1であり、 The rare earth element RE is selected from at least one of Gd, Lu, Y, Sc, La, Nd, Eu, Tb, Dy, Ho, Er, Tm, and Yb; The A is selected from at least one of Li, Mg, Ca, K, and Na; The D is selected from at least one of Ga and In, The M is a transition metal element and is at least one selected from the group consisting of Cr, Mn, Fe, Co, and Ni.
[0010] In the present invention, the ionic radius and electronegativity are Al 3+ Compared with Gd, these transition metal elements (at least one of Cr, Mn, Fe, Co, and Ni) preferentially occupy the Al site, and the ionic radius, electronegativity, etc. are similar to those of Al. 3+and have a smaller effect on the surrounding crystal field. At the same time, the electron configuration of these transition metal elements is [Ar]3d n 4s 1 ~ 2 (n≧5) and the exonuclear electron configuration of the Ce atom is [Xe]4f 1 5d 1 6s 2 When the co-doping atom and the Ce atom are close to each other, Ce tends to form a stable +4 valence, thereby accelerating the scintillation decay and improving the quality factor. By doping with a transition metal element, a faster luminescence decay rate is achieved, including at least one shortening of the decay time of photoluminescence or scintillation luminescence. More preferably, in addition to the faster decay time, at least one of improved light output, better energy resolution, and reduced afterglow is also accompanied. The present invention produces a new scintillation material with high quality factor and ultrafast luminescence performance, which better meets the demands of high energy physics, space physics, industrial non-destructive testing, safety auditing, mineral and oil well exploration, and nuclear medicine imaging (X-CT, TOF-PET).
[0011] Preferably, z is in the range of 0.00001≦z≦0.05.
[0012] Preferably, x is 0.001 <x≦0.05である。
[0013] Preferably, the transition metal element-doped garnet structure aluminate scintillation material is a transition metal element-doped garnet structure aluminate scintillation polycrystal powder, a transition metal element-doped garnet structure aluminate scintillation ceramic, or a transition metal element-doped garnet structure aluminate scintillation single crystal.
[0014] In the second aspect, the present invention provides a method for preparing a transition metal element-doped garnet-structure aluminate scintillation material, the chemical formula of the transition metal element-doped garnet-structure aluminate scintillation material is: 3-x-a Ce x A aAl 5-y-z D y M z O 12 wherein x is 0 < x ≤ 0.15, y is 0 ≤ y ≤ 3, z is 0 < z ≤ 0.1, a is 0 ≤ a ≤ 0.1; the rare earth element RE is selected from at least one of Gd, Lu, Y, Sc, La, Nd, Eu, Tb, Dy, Ho, Er, Tm, Yb; the A is selected from at least one of Li, Mg, Ca, K, Na; the D is selected from at least one of Ga, In; the M is a transition metal element and is selected from at least one of Cr, Mn, Fe, Co, Ni, When the transition metal element-doped garnet structure aluminate scintillation material is a transition metal element-doped garnet structure aluminate scintillation polycrystalline powder, its manufacturing method is as follows, (1) Weighing CeO2, Al2O3, the oxide of RE, the oxide of D, and the oxide of M according to the chemical formula of the transition metal element-doped garnet structure aluminate scintillation polycrystalline powder, and mixing them to obtain a mixed powder; (2A) Performing a solid-phase reaction on the mixed powder to obtain the transition metal element-doped garnet structure aluminate scintillation polycrystalline powder.
[0015] Preferably, before mixing, the raw materials are pre-fired, and the pre-firing is carried out at a temperature of 1100 °C for 20 hours. The solid-phase reaction is carried out at a temperature of 1200 - 2000 °C for 5 - 200 hours.
[0016] In a third aspect, the present invention provides a method for manufacturing a transition metal element-doped garnet structure aluminate scintillation material, and the chemical formula of the transition metal element-doped garnet structure aluminate scintillation material is RE 3-x-a Ce x A a Al 5-y-z D y M z O 12wherein x is 0 < x ≤ 0.15, y is 0 ≤ y ≤ 3, z is 0 < z ≤ 0.1, a is 0 ≤ a ≤ 0.1, the rare earth element RE is selected from at least one of Gd, Lu, Y, Sc, La, Nd, Eu, Tb, Dy, Ho, Er, Tm, Yb, the A is selected from at least one of Li, Mg, Ca, K, Na, the D is selected from at least one of Ga, In, and the M is a transition metal element selected from at least one of Cr, Mn, Fe, Co, Ni. When the transition metal element-doped garnet structure aluminate scintillation material is a transition metal element-doped garnet structure aluminate scintillation ceramic, its manufacturing method is as follows. (1) According to the chemical formula of the transition metal element-doped garnet structure aluminate scintillation polycrystalline powder, weighing CeO2, Al2O3, the oxide of RE, the oxide of D, and the oxide of M as raw materials, and mixing them to obtain a mixed powder. (2B) After forming the mixed powder into a compact, sintering it to obtain the transition metal element-doped garnet structure aluminate scintillation ceramic.
[0017] Preferably, before mixing, the raw materials are pre-fired, and the pre-firing is carried out at a temperature of 1100 °C for 20 hours. The forming method of the compact includes at least one of dry pressing forming and cold isostatic pressing forming. Preferably, the pressure of the dry pressing forming is 10 - 35 MPa, and the pressure of the cold isostatic pressing forming is 2 - 5 GPa. The sintering method is at least one of non-pressure sintering, hot pressing sintering, and hot isostatic pressing sintering. Preferably, the non-pressure sintering is carried out at a temperature of 1200 - 2000 °C for 5 - 200 hours.
[0018] In a fourth aspect, the present invention provides a method for manufacturing a transition metal element-doped garnet structure aluminate scintillation material. The chemical formula of the transition metal element-doped garnet structure aluminate scintillation material is RE 3-x-a Cex A a Al 5-y-z D y M z O 12 wherein x is 0 < x ≤ 0.15, y is 0 ≤ y ≤ 3, z is 0 < z ≤ 0.1, a is 0 ≤ a ≤ 0.1, the rare earth element RE is selected from at least one of Gd, Lu, Y, Sc, La, Nd, Eu, Tb, Dy, Ho, Er, Tm, Yb, A is selected from at least one of Li, Mg, Ca, K, Na, D is selected from at least one of Ga, In, and M is a transition metal element selected from at least one of Cr, Mn, Fe, Co, Ni. When the transition metal element doped garnet structure aluminate scintillation material is a transition metal element doped garnet structure aluminate scintillation single crystal, its manufacturing method is as follows. (1) According to the chemical formula of the transition metal element doped garnet structure aluminate scintillation polycrystalline powder, weighing CeO2, Al2O3, the oxide of RE, the oxide of D, and the oxide of M as raw materials, and mixing them to obtain a mixed powder. (2C) Melting the mixed powder by heating to initiate the growth of a single crystal. The single crystal growth method includes any one of the Czochralski method, the Bridgman method, the temperature gradient method, the heat exchange method, the Kyropoulos method, the top-seeded solution growth method, the flux method, and the micro-pulling method.
[0019] Preferably, before mixing, the raw materials are pre-fired. The pre-firing is carried out at a temperature of 1100 °C for 20 hours. The heating method is resistance heating, electromagnetic induction heating, or light heating. The parameters of the Czochralski method include parameter design of required dimensions, temperature field design, PID quality control temperature, pulling speed, and rotation speed. The parameters of the Bridgman method include parameter design of required dimensions, temperature field design, and growth rate.
[0020] In the fifth aspect, the present invention provides the application of the above-mentioned transition metal element-doped garnet-structure aluminate scintillation material in high energy physics, space physics, industrial non-destructive testing, safety auditing, mineral and oil well exploration, and nuclear medicine imaging (X-CT, TOF-PET). Effect of the Invention
[0021] 1. The present invention proposes a technical solution for a garnet-structure aluminate scintillation material doped with a transition metal element whose ionic radius and electronegativity are similar to those of Al3+, and selects suitable doping ions based on reasonable prediction and experimental verification. 2. In the present invention, after the garnet structure aluminate scintillation material is doped with transition metal elements, the luminescence performance of the material is greatly improved, including but not limited to the quality factor (light yield / scintillation decay time) related to the scintillation performance is greatly improved, the scintillation rise time or decay time is shortened, and the afterglow level is greatly reduced. 3. In the present invention, the transition metal elements are doped into the garnet structure aluminate scintillation material to obtain a high quality factor scintillation material, which can be better applied in high energy physics, space physics, industrial non-destructive testing, safety auditing, mineral and oil well exploration, and nuclear medicine imaging (X-CT, TOF-PET). [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a scintillation decay time spectrum of the single crystal of Example 18. [Diagram 2] FIG. 2 is a multichannel energy spectrum of the single crystal of Example 18. [Diagram 3] FIG. 3 is an X-ray excitation spectrum of the single crystal of Example 18. [Figure 4] FIG. 4 shows the afterglow decay spectrum of the single crystal of Example 18. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be further described through the following embodiments. The following embodiments are provided to illustrate the present invention and are not intended to limit the present invention.
[0024] In the present disclosure, GAGG:Ce includes, for example, Cr, Mn, Fe, Co, Ni, etc., which have a radius, ionic radius, and electronegativity of Al. 3+ The doping elements preferentially occupy the Al site rather than Gd, and their ionic radii, electronegativities, etc. are more similar to those of Al, and their influence on the surrounding crystal field is smaller. At the same time, the electron configuration of these transition metal elements is [Ar]3d n 4s 1 ~ 2 (n≧5) and the exonuclear electron configuration of the Ce atom is [Xe]4f 1 5d 1 6s 2 When the co-doping atom and the Ce atom are close to each other, Ce tends to form a stable +4 valence, thereby accelerating the scintillation decay and significantly improving the quality factor. The method is generally applicable to garnet-structured aluminate scintillation materials, and is expected to obtain novel component materials with excellent performance. The method is generally applicable to garnet-structured aluminate scintillation materials, and is of great significance in improving the scintillation performance of garnet-structured aluminate scintillation materials, and is expected to obtain novel component materials with excellent performance.
[0025] In addition to the remarkable improvement of the quality factor, the present invention is accompanied by at least one of the following: a shortened scintillation rise time, a significant reduction in the afterglow level, an improvement in the energy resolution, and an increase in the fluorescence emission intensity or the X-ray excited emission intensity. If the z value is too high, the performance of the quality factor, energy resolution, afterglow, fluorescence emission intensity, or X-ray excited emission intensity will be deteriorated.
[0026] In the present disclosure, the chemical formula of the transition metal element-doped garnet-structure aluminate scintillation material is:3-x-a Ce x A a Al 5-y-z D y M z O 12 wherein x is 0 < x ≤ 0.15, y is 0 ≤ y ≤ 3, z is 0 < z ≤ 0.1, and a may be 0 ≤ a ≤ 0.1. The rare earth element RE is selected from at least one of Gd, Lu, Y, Sc, La, Nd, Eu, Tb, Dy, Ho, Er, Tm, and Yb. The D is selected from one of Ga and In. The M is a co-doping element and is selected from at least one of Cr, Mn, Fe, Co, and Ni. In any embodiment, RE 3-x Ce x Al 5-y-z D y M z O 12 Another A element dopant may be added to RE and incorporated into the rare earth RE lattice site. The A element specifically includes at least one of Li, Mg, Ca, K, and Na. Preferably, the garnet structure aluminates scintillation material improved by doping the transition metal element is polycrystalline powder, ceramics, or single crystal.
[0027] In any embodiment, when RE is Gd, D is Ga, and M is Cr, z is 0.003 ≤ z ≤ 0.05. When RE is Gd, D is Ga, and M is Mn, z is 0.0002 ≤ z ≤ 0.05. When RE is Gd, D is Ga, and M is Fe, z is 0.003 ≤ z ≤ 0.05. When RE is Gd, D is Ga, and M is Co, z is 0.003 ≤ z ≤ 0.05. When RE is Gd, D is Ga, and M is Ni, z is 0.001 ≤ z ≤ 0.05.
[0028] In any embodiment, when RE is Lu and M is Cr, z is 0.001 ≤ z ≤ 0.05. When RE is Lu and M is Mn, z is 0.0004 ≤ z ≤ 0.05. When RE is Lu and M is Fe, z is 0.003 ≤ z ≤ 0.05. When RE is Lu and M is Co, z is 0.001 ≤ z ≤ 0.05. When RE is Lu and M is Ni, z is 0.0006 ≤ z ≤ 0.05.
[0029] In any embodiment, when RE is Y and M is Cr, z is 0.003≦z≦0.05; when RE is Y and M is Mn, z is 0.0004≦z≦0.05; when RE is Y and M is Fe, z is 0.001≦z≦0.05; when RE is Y and M is Co, z is 0.0006≦z≦0.05; and when RE is Y and M is Ni, z is 0.0006≦z≦0.05.
[0030] The following is an exemplary method for preparing the improved garnet-structure aluminate scintillation material doped with transition metal elements provided in the present invention. The obtained garnet-structure aluminate scintillation material doped with transition metal elements is polycrystalline powder or ceramic or single crystal, among which ceramic includes transparent ceramic and non-transparent ceramic.
[0031] CeO2, Al2O3, rare earth oxides (RE m O n ), Ga or In oxide (D2O3) is used as the raw material, and the molar ratio of the raw material components is RE m O n The raw materials were mixed according to the following ratio: CeO2:Al2O3:D2O3=(3-x) / m:x:(5-yz) / 2:y / 2, and thoroughly mixed to obtain a mixed powder. The purity of the raw materials used was 99.99% (4N) or higher. Preferably, before mixing, the starting materials were placed in a muffle furnace in an air atmosphere and fired at 1100°C for 20 hours to remove adsorbed water, crystallization water, and some organic matter (such as oxalate ions that may remain in the rare earth raw materials) from the raw materials.
[0032] The mixed powder may be directly fired at 1200-2000°C for 5-200 hours to cause a solid-state reaction to obtain a polycrystalline powder. Preferably, the solid-state reaction may be performed at a temperature of 1400-1600°C for 10-50 hours. In any embodiment, in the production of the garnet-structure aluminate scintillation polycrystalline powder, the obtained ceramics and single crystals may be crushed to obtain powder.
[0033] The mixed powder may be directly pressed into a block shape by cold isostatic pressing (pressure 2-5 GPa) and sintered at 1200-2000°C for 5-200 hours to obtain ceramics. Alternatively, the sintering process may be adjusted to produce transparent ceramics, for example, hot press sintering or vacuum sintering. The pressure for pressing into a block may be 2-5 GPa. Preferably, the solid-state reaction may be performed at a temperature of 1400-1600°C for 10-50 hours.
[0034] The mixed powder or polycrystalline powder is put into a container, melted by heating (resistance heating, electromagnetic induction heating, light heating, etc.), and slowly crystallized from the melt to produce a single crystal. Specific methods include growing by the Czochralski method, Bridgman method, temperature gradient method, heat exchange method, Kyropoulos method, top-seeded solution growth method, flux method, and micro-pulling down method (μ-PD). The container used may be a graphite crucible, an iridium crucible, a molybdenum crucible, a tungsten-molybdenum crucible, a rhenium crucible, a tantalum crucible, an alumina crucible, or a zirconia crucible. The atmosphere for growing the single crystal may be one or more of air, argon, nitrogen, carbon dioxide, and carbon monoxide, or a mixture of these. In any embodiment, the single crystal is grown by the Czochralski method, the container is an iridium crucible, induction heating is used, the growth atmosphere is high purity nitrogen, and the crystal is pulled up while rotating, more preferably, the pulling speed for growing the single crystal by the Czochralski method is 0.7 to 6.0 mm / h, and the rotation speed is 3 to 15 r / min.
[0035] In this application, when preparing the transition metal element-doped garnet structure aluminate scintillation material, a very small amount of doping element M is doped into the rare earth RE site, but due to technical limitations, it is difficult to obtain the exact doping content by common characterization means. Naturally, even if a very small amount of doping element M is doped into the rare earth RE site, there is no fundamental change in the performance of the material itself. In addition, the obtained transition metal element-doped garnet structure aluminate scintillation material has a high quality factor and can be better applied in high energy physics, space physics, industrial non-destructive testing, safety auditing, mineral and oil well exploration, and nuclear medicine imaging (X-CT, TOF-PET).
[0036] The present invention will be described in more detail through the following examples. Similarly, the following examples are provided to further explain the present invention and do not limit the scope of the present invention. Non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention are both within the scope of the present invention. Specific process variables in the following examples are merely examples within the applicable range, that is, those skilled in the art can select within an appropriate range based on the description of the present invention, and are not limited to the specific numerical values in the following examples.
[0037] Example 1 (Growth of Cr-doped GAGG:Ce single crystals by the Czochralski method) Single crystals were grown using the Czochralski method. The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Cr2O3 = 1.485:0.03:(2.3-z) / 2:1.35:z / 2 (z = 0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1) was mixed thoroughly and uniformly, and the mixture was then cold isostatically pressed (pressure 3 GPa). The pressed block is placed in an iridium crucible, and is then fully melted by induction heating under a nitrogen protective atmosphere. After seed crystal inoculation, the block is gradually pulled out of the melt to grow a single crystal of a desired size. 2.97 Ce 0.03Al 2.3-z Ga 2.7 Cr z O 12 Single crystals were obtained, among which the parameters of the Czochralski method include the parameter design of the required dimensions, the temperature field design, the PID quality control temperature, the pulling speed is 0.7-6.0mm / h, and the rotation speed is 3-15r / min.
[0038] Example 2 (Growth of Cr-doped GAGG:Ce single crystals by the micro-pulling down method) Single crystals were grown using the micro-pulling down method. The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Cr2O3=1.4925:0.015:(2.3-z) / 2:1.35:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1) was mixed thoroughly and uniformly, and then pre-sintered at 1450℃ using a muffle furnace. The sintered raw materials were placed in an iridium crucible, and melted thoroughly by induction heating under nitrogen gas as a protective atmosphere. After the seed crystal was brought into contact with the melt, it was slowly pulled down and Gd 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Cr z O 12 A single crystal was obtained, among which the parameters of the micro-pulling down process include the required size parameter design, temperature field design, and the micro-pulling down process speed is 3-20mm / h.
[0039] Example 3 (Preparation of Cr-doped GAGG:Ce polycrystalline powder) The mixture was mixed thoroughly and uniformly according to Example 2, then placed in an alumina crucible and fired at 1600°C for 10 hours in a muffle furnace to carry out a sufficient solid-state reaction to obtain Gd 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Cr z O 12 A polycrystalline powder was obtained.
[0040] Example 4 (Preparation of Cr-doped GAGG:Ce ceramics) Non-transparent: The formulation was carried out according to Example 2, and the powder was thoroughly and uniformly mixed, and then pressed into a block by cold isostatic pressing (pressure 3 GPa). The pressed block was placed in an alumina crucible and sintered at 1600 °C for 10 h in a muffle furnace to carry out a sufficient solid-state reaction to form Gd 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Cr z O 12 Non-transparent ceramics were obtained. Transparent: The powder is mixed thoroughly and uniformly according to Example 2, then pressed under cold isostatic pressure (3 GPa pressure), and then subjected to a sufficient solid-state reaction (1600°C, 50 h) in a vacuum hot press furnace to remove air bubbles and voids as much as possible, and the Gd 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Cr z O 12 Transparent ceramics were obtained.
[0041] Example 5 (Growth of Mn-doped GAGG:Ce single crystals by the Czochralski method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Mn2O3 was 1.485:0.03:(2.3-z) / 2:1.35:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 1, and Gd 2.97 Ce 0.03 Al 2.3-z Ga 2.7 Mn z O 12 A single crystal was obtained.
[0042] Example 6 (Growth of Mn-doped GAGG:Ce single crystals by the micro-pulling down method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Mn2O3 was 1.4925:0.015:(2.3-z) / 2:1.35:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 2, to obtain Gd 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Mn z O 12 A single crystal was obtained.
[0043] Example 7 (Preparation of Mn-doped GAGG:Ce polycrystalline powder) The compounding was carried out according to Example 6, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Mn z O 12 A polycrystalline powder was obtained.
[0044] Example 8 (Preparation of Mn-doped GAGG:Ce ceramics) The compounding was carried out according to Example 6, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Mn z O 12 Non-transparent and transparent ceramics were obtained.
[0045] Example 9 (Growth of Fe-doped GAGG:Ce single crystals by the Czochralski method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Fe2O3 = 1.485:0.03:(2.3-z) / 2:1.35:z / 2 (z = 0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1) was used. The next step was the same as in Example 1, and Gd 2.97 Ce 0.03 Al 2.3-z Ga 2.7 Fe z O 12 A single crystal was obtained.
[0046] Example 10 (Growth of Fe-doped GAGG:Ce single crystals by the micro-pulling down method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Fe2O3 = 1.4925:0.015:(2.3-z) / 2:1.35:z / 2 (z = 0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1) was used. The next step was the same as in Example 2, and Gd 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Fe z O 12 A single crystal was obtained.
[0047] Example 11 (Preparation of Fe-doped GAGG:Ce polycrystalline powder) The compounding was carried out according to Example 10, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Fe z O 12 A polycrystalline powder was obtained.
[0048] Example 12 (Preparation of Fe-doped GAGG:Ce ceramics) The compounding was carried out according to Example 10, and the next step was the same as in Example 4,2.985 Ce 0.015 Al 2.3-z Ga 2.7 Fe z O 12 Non-transparent and transparent ceramics were obtained.
[0049] Example 13 (Growth of Co-doped GAGG:Ce single crystals by the Czochralski method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:CoO was 1.485:0.03:(2.3-z) / 2:1.35:z (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 1, and Gd 2.97 Ce 0.03 Al 2.3-z Ga 2.7 Co z O 12 A single crystal was obtained.
[0050] Example 14 (Growth of Co-doped GAGG:Ce single crystals by the micro-pulling down method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:CoO was 1.4925:0.015:(2.3-z) / 2:1.35:z (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 2, and Gd 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Co z O 12 A single crystal was obtained.
[0051] Example 15 (Preparation of Co-doped GAGG:Ce polycrystalline powder) The compounding was carried out according to Example 14, and the next step was the same as in Example 3, 2.985 Ce 0.015Al 2.3-z Ga 2.7 Co z O 12 A polycrystalline powder was obtained.
[0052] Example 16 (Preparation of Co-doped GAGG:Ce ceramics) The compounding was carried out according to Example 14, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Co z O 12 Non-transparent and transparent ceramics were obtained.
[0053] Example 17 (Growth of Ni-doped GAGG:Ce single crystals by the Czochralski method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Ni2O3 was 1.485:0.03:(2.3-z) / 2:1.35:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 1, and Gd 2.97 Ce 0.03 Al 2.3-z Ga 2.7 Ni z O 12 A single crystal was obtained.
[0054] Example 18 (Growth of Ni-doped GAGG:Ce single crystals by the micro-pulling down method) The molar ratio of Gd2O3:CeO2:Al2O3:Ga2O3:Ni2O3 was 1.4925:0.015:(2.3-z) / 2:1.35:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 2, and Gd 2.985 Ce 0.015 Al 2.3-zGa 2.7 Ni z O 12 A single crystal was obtained.
[0055] Example 19 (Preparation of Ni-doped GAGG:Ce polycrystalline powder) The compounding was carried out according to Example 18, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Ni z O 12 A polycrystalline powder was obtained.
[0056] Example 20 (Preparation of Ni-doped GAGG:Ce ceramics) The compounding was carried out according to Example 18, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 2.3-z Ga 2.7 Ni z O 12 Non-transparent and transparent ceramics were obtained.
[0057] Example 21 (Growth of Cr-doped LuAG:Ce single crystals by the Czochralski method) The molar ratio of Lu2O3:CeO2:Al2O3:Cr2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z = 0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 1, to obtain Lu 2.97 Ce 0.03 Al 5-z Cr z O 12 A single crystal was obtained.
[0058] Example 22 (Growth of Cr-doped LuAG:Ce single crystals by the micro-pulling down method) The molar ratio of Lu2O3:CeO2:Al2O3:Cr2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 2, 2.985 Ce 0.015 Al 5-z Cr z O 12 A single crystal was obtained.
[0059] Example 23 (Preparation of Cr-doped LuAG:Ce polycrystalline powder) The compounding was carried out according to Example 22, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Cr z O 12 A polycrystalline powder was obtained.
[0060] Example 24 (Preparation of Cr-doped LuAG:Ce ceramics) The compounding was carried out according to Example 22, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Cr z O 12 Non-transparent and transparent ceramics were obtained.
[0061] Example 25 (Growth of Mn-doped LuAG:Ce single crystals by the Czochralski method) The molar ratio of Lu2O3:CeO2:Al2O3:Mn2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 1, 2.97 Ce 0.03 Al 5-z Mn z O12 A single crystal was obtained.
[0062] Example 26 (Growth of Mn-doped LuAG:Ce single crystals by the micro-pulling down method) The molar ratio of Lu2O3:CeO2:Al2O3:Mn2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 2, to obtain Lu 2.985 Ce 0.015 Al 5-z Mn z O 12 A single crystal was obtained.
[0063] Example 27 (Preparation of Mn-doped LuAG:Ce polycrystalline powder) The compounding was carried out according to Example 26, and the next step was carried out as in Example 3, to obtain Lu 2.985 Ce 0.015 Al 5-z Mn z O 12 A polycrystalline powder was obtained.
[0064] Example 28 (Preparation of Mn-doped LuAG:Ce ceramics) The compounding was carried out according to Example 26, and the next step was carried out as in Example 4, to obtain Lu 2.985 Ce 0.015 Al 5-z Mn z O 12 Non-transparent and transparent ceramics were obtained.
[0065] Example 29 (Growth of Fe-doped LuAG:Ce single crystals by the Czochralski method) The molar ratio of Lu2O3:CeO2:Al2O3:Fe2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 1, 2.97 Ce 0.03 Al 5-z Fe z O 12 A single crystal was obtained.
[0066] Example 30 (Growth of Fe-doped LuAG:Ce single crystals by the micro-pulling down method) The molar ratio of Lu2O3:CeO2:Al2O3:Fe2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 2, 2.985 Ce 0.015 Al 5-z Fe z O 12 A single crystal was obtained.
[0067] Example 31 (Preparation of Fe-doped LuAG:Ce polycrystalline powder) The compounding was carried out according to Example 30, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Fe z O 12 A polycrystalline powder was obtained.
[0068] Example 32 (Preparation of Fe-doped LuAG:Ce ceramics) The compounding was carried out according to Example 30, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Fe z O 12Non-transparent and transparent ceramics were obtained.
[0069] Example 33 (Growth of Co-doped LuAG:Ce single crystals by the Czochralski method) The molar ratio of Lu2O3:CeO2:Al2O3:CoO was 1.485:0.03:(5-z) / 2:z (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 1, to obtain Lu 2.97 Ce 0.03 Al 5-z Co z O 12 A single crystal was obtained.
[0070] Example 34 (Growth of Co-doped LuAG:Ce single crystals by the micro-pulling down method) The molar ratio of Lu2O3:CeO2:Al2O3:CoO was 1.4925:0.015:(5-z) / 2:z (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 2, and Lu 2.985 Ce 0.015 Al 5-z Co z O 12 A single crystal was obtained.
[0071] Example 35 (Preparation of Co-doped LuAG:Ce polycrystalline powder) The compounding was carried out according to Example 34, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Co z O 12 A polycrystalline powder was obtained.
[0072] Example 36 (Preparation of Co-doped LuAG:Ce ceramics) The compounding was carried out according to Example 34, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Co z O 12 Non-transparent and transparent ceramics were obtained.
[0073] Example 37 (Growth of Ni-doped LuAG:Ce single crystals by the Czochralski method) The molar ratio of Lu2O3:CeO2:Al2O3:Ni2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 1, 2.97 Ce 0.03 Al 5-z Ni z O 12 A single crystal was obtained.
[0074] Example 38 (Growth of Ni-doped LuAG:Ce single crystals by the micro-pulling-down method) The molar ratio of Lu2O3:CeO2:Al2O3:Ni2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 2, 2.985 Ce 0.015 Al 5-z Ni z O 12 A single crystal was obtained.
[0075] Example 39 (Preparation of Ni-doped LuAG:Ce polycrystalline powder) The compounding was carried out according to Example 38, and the next step was carried out as in Example 3, 2.985 Ce 0.015 Al 5-z Niz O 12 A polycrystalline powder was obtained.
[0076] Example 40 (Preparation of Ni-doped LuAG: Preparation of Ce ceramics) The compounding was carried out according to Example 38, and the next step was carried out as in Example 4, to obtain Lu 2.985 Ce 0.015 Al 5-z Ni z O 12 Non-transparent and transparent ceramics were obtained.
[0077] Example 41 (Growth of Cr-doped YAG:Ce single crystals by the Czochralski method) The molar ratio of Y2O3:CeO2:Al2O3:Cr2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 1, and Y 2.97 Ce 0.03 Al 5-z Cr z O 12 A single crystal was obtained.
[0078] Example 42 (Growth of Cr-doped YAG:Ce single crystals by the micro-pulling down method) The molar ratio of Y2O3:CeO2:Al2O3:Cr2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 2, and Y 2.985 Ce 0.015 Al 5-z Cr z O 12 A single crystal was obtained.
[0079] Example 43 (Preparation of Cr-doped YAG:Ce polycrystalline powder) The compounding was carried out according to Example 42, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Cr z O 12 A polycrystalline powder was obtained.
[0080] Example 44 (Preparation of Cr-doped YAG:Ce ceramics) The compounding was carried out according to Example 42, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Cr z O 12 Non-transparent and transparent ceramics were obtained.
[0081] Example 45 (Growth of Mn-doped YAG:Ce single crystals by the Czochralski method) The molar ratio of Y2O3:CeO2:Al2O3:Mn2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 1, 2.97 Ce 0.03 Al 5-z Mn z O 12 A single crystal was obtained.
[0082] Example 46 (Growth of Mn-doped YAG:Ce single crystals by the micro-pulling down method) The molar ratio of Y2O3:CeO2:Al2O3:Mn2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 2, 2.985 Ce0.015 Al 5-z Mn z O 12 A single crystal was obtained.
[0083] Example 47 (Preparation of Mn-doped YAG:Ce polycrystalline powder) The compounding was carried out according to Example 46, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Mn z O 12 A polycrystalline powder was obtained.
[0084] Example 48 (Preparation of Mn-doped YAG:Ce ceramics) The compounding was carried out according to Example 46, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Mn z O 12 Non-transparent and transparent ceramics were obtained.
[0085] Example 49 (Growth of Fe-doped YAG:Ce single crystals by the Czochralski method) The molar ratio of Y2O3:CeO2:Al2O3:Fe2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 1, and Y 2.97 Ce 0.03 Al 5-z Fe z O 12 A single crystal was obtained.
[0086] Example 50 (Growth of Fe-doped YAG:Ce single crystals by the micro-pulling down method) The molar ratio of Y2O3:CeO2:Al2O3:Fe2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 2, and Y 2.985 Ce 0.015 Al 5-z Fe z O 12 A single crystal was obtained.
[0087] Example 51 (Preparation of Fe-doped YAG:Ce polycrystalline powder) The compounding was carried out according to Example 50, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Fe z O 12 A polycrystalline powder was obtained.
[0088] Example 52 (Preparation of Fe-doped YAG:Ce ceramics) The compounding was carried out according to Example 50, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Fe z O 12 Non-transparent and transparent ceramics were obtained.
[0089] Example 53 (Growth of Co-doped YAG:Ce single crystals by the Czochralski method) The molar ratio of Y2O3:CeO2:Al2O3:CoO was 1.485:0.03:(5-z) / 2:z (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 1, and Y 2.97 Ce 0.03 Al 5-z Co z O 12A single crystal was obtained.
[0090] Example 54 (Growth of Co-doped YAG:Ce single crystals by the micro-pulling down method) The molar ratio of Y2O3:CeO2:Al2O3:CoO was 1.4925:0.015:(5-z) / 2:z (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 2, and Y 2.985 Ce 0.015 Al 5-z Co z O 12 A single crystal was obtained.
[0091] Example 55 (Preparation of Co-doped YAG:Ce polycrystalline powder) The compounding was carried out according to Example 54, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Co z O 12 A polycrystalline powder was obtained.
[0092] Example 56 (Preparation of Co-doped YAG:Ce ceramics) The compounding was carried out according to Example 54, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Co z O 12 Non-transparent and transparent ceramics were obtained.
[0093] Example 57 (Growth of Ni-doped YAG:Ce single crystals by the Czochralski method) The molar ratio of Y2O3:CeO2:Al2O3:Ni2O3 was 1.485:0.03:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1). The next step was the same as in Example 1, and Y 2.97 Ce 0.03 Al 5-z Ni z O 12 A single crystal was obtained.
[0094] Example 58 (Growth of Ni-doped YAG:Ce single crystals by the micro-pulling down method) The molar ratio of Y2O3:CeO2:Al2O3:Ni2O3 was 1.4925:0.015:(5-z) / 2:z / 2 (z=0.00001, 0.00005, 0.0001, 0.0002, 0.0004, 0.0006, 0.0008, 0.001, 0.002, 0.003, 0.005, 0.007, 0.01, 0.03, 0.05, 0.07, 0.1), and the next step was the same as in Example 2, 2.985 Ce 0.015 Al 5-z Ni z O 12 A single crystal was obtained.
[0095] Example 59 (Preparation of Ni-doped YAG:Ce polycrystalline powder) The compounding was carried out according to Example 58, and the next step was the same as in Example 3, 2.985 Ce 0.015 Al 5-z Ni z O 12 A polycrystalline powder was obtained.
[0096] Example 60 (Preparation of Ni-doped YAG:Ce ceramics) The compounding was carried out according to Example 58, and the next step was the same as in Example 4, 2.985 Ce 0.015 Al 5-z Ni z O 12Non-transparent and transparent ceramics were obtained.
[0097] Table 1 shows the relative light yield and quality factor (light yield / scintillation decay time) of the single crystal of Example 18.
[0098] [Table 1]
[0099] Table 2 shows the afterglow levels of the single crystals of Example 18.
[0100] [Table 2]
[0101] Table 3 shows the relative quality factors of the non-transparent ceramics of Examples 4, 8, 12, 16 and 20 (compared to non-codoped non-transparent ceramic sheets).
[0102] [Table 3]
[0103] Table 4 shows the relative quality factors of the non-transparent ceramics of Examples 24, 28, 32, 36 and 40 (compared to non-codoped non-transparent ceramic sheets).
[0104] [Table 4]
[0105] Table 5 shows the relative quality factors of the non-transparent ceramics of Examples 44, 48, 52, 56 and 60 (compared to non-codoped non-transparent ceramic sheets).
[0106] [Table 5]
[0107] In the present invention, GAGG:Ce has an ionic radius and electronegativity of Al 3+ The doping elements preferentially occupy the Al site over Gd, and the ionic radius and electronegativity are similar to those of Al. 3+ and have a smaller effect on the surrounding crystal field. At the same time, the electron configuration of these transition metal elements is [Ar]3d n 4s 1 ~ 2 (n≧5) and the exonuclear electron configuration of the Ce atom is [Xe]4f 1 5d 1 6s 2 When the co-doping atom and the Ce atom are close to each other, Ce tends to form a stable +4 valence, thereby accelerating the scintillation decay and improving the quality factor. The method is generally applicable to garnet-structured aluminate scintillation materials and can provide guidance for the design of new components.
[0108] Similarly, the above examples are for the purpose of further illustrating the present invention, and do not limit the scope of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention both belong to the scope of the present invention.
Claims
1. The chemical formula is: 3-x-a C.E. x A a A 5-y-z D y M z O 12 wherein x is 0<x≦0.15, y is 0≦y≦3, z is 0<z≦0.1, and a is 0≦a≦0.1; The RE is a rare earth element selected from at least one of Gd, Lu, Y, Sc, La, Nd, Eu, Tb, Dy, Ho, Er, Tm, and Yb; The A is selected from at least one of Li, Mg, Ca, K, and Na; The D is selected from at least one of Ga and In, The M is a transition metal element selected from at least one of Cr, Mn, Fe, Co, and Ni; A transition metal element-doped garnet-structure aluminate scintillation material.
2. 2. The transition metal element-doped garnet-structure aluminate scintillation material according to claim 1, wherein z satisfies 0.00001≦z≦0.
05.
3. 3. The transition metal element-doped garnet-structure aluminate scintillation material according to claim 1, wherein x satisfies the condition 0.001<x≦0.
05.
4. 3. The transition metal element-doped garnet-structure aluminate scintillation material according to claim 1 or 2, characterized in that the transition metal element-doped garnet-structure aluminate scintillation material is a transition metal element-doped garnet-structure aluminate scintillation polycrystalline powder, a transition metal element-doped garnet-structure aluminate scintillation ceramic, or a transition metal element-doped garnet-structure aluminate scintillation single crystal.
5. The chemical formula of the transition metal element-doped garnet structure aluminate scintillation material is RE 3-x-a C.E. x A a A 5-y-z D y M z O 12 and wherein x is 0<x≦0.15, y is 0≦y≦3, z is 0<z≦0.1, and a is 0≦a≦0.1; RE is a rare earth element selected from at least one of Gd, Lu, Y, Sc, La, Nd, Eu, Tb, Dy, Ho, Er, Tm, and Yb; A is selected from at least one of Li, Mg, Ca, K, and Na; D is selected from at least one of Ga and In; and M is a transition metal element selected from at least one of Cr, Mn, Fe, Co, and Ni; The manufacturing method is When the transition metal element-doped garnet-structure aluminate scintillation material is a polycrystalline powder, (1) CeO according to the above chemical formula 2 , Al 2 O 3 Weighing out and mixing the oxides of RE, D, and M as raw materials to obtain a mixed powder; (2A) subjecting the mixed powder to a solid-state reaction to obtain the transition metal element-doped garnet-structure aluminate scintillation polycrystalline powder, the solid-state reaction being performed at a temperature of 1200-2000° C. for a time of 5-200 hours; When the transition metal element-doped garnet-structure aluminate scintillation material is a ceramic, (1) CeO according to the above chemical formula 2 , Al 2 O 3 Weighing out and mixing the oxides of RE, D, and M as raw materials to obtain a mixed powder; (2B) forming the mixed powder into a molded body, and then sintering the molded body to obtain the transition metal element-doped garnet-structure aluminate scintillation ceramics, the molding method of the molded body being at least one of dry pressing and cold isostatic pressing, the pressure of the dry pressing is 10-35 MPa, the pressure of the cold isostatic pressing is 2-5 GPa, the sintering method being at least one of pressureless sintering, hot pressure sintering, and hot isostatic sintering, the pressureless sintering is performed at a temperature of 1200-2000°C and for a time of 5-200 hours; When the transition metal element-doped garnet-structure aluminate scintillation material is a single crystal, (1) CeO according to the above chemical formula 2 , Al 2 O 3 Weighing out and mixing the oxides of RE, D, and M as raw materials to obtain a mixed powder; (2C) melting the mixed powder by heating to start the growth of a single crystal, the method of growing the single crystal including any one of the Czochralski method, the Bridgman method, the temperature gradient method, the heat exchange method, the Kyropoulos method, the top-seeded solution growth method, the flux method, and the micro-pulling down method, and the method of heating is resistance heating, electromagnetic induction heating, or light heating. A method for producing a transition metal element-doped garnet-structure aluminate scintillation material.
6. The method according to claim 5, further comprising pre-firing the raw materials before mixing, the pre-firing being performed at a temperature of 1100°C for 20 hours.
7. The application of the transition metal element doped garnet structure aluminate scintillation material according to claim 1 in high energy physics, space physics, industrial non-destructive testing, safety audit, mineral and oil well exploration, and nuclear medicine imaging.
Citation Information
Patent Citations
Manganese-doped yttrium aluminium garnet monocrystal material and application for same
CN103059860A
Oxide phosphor, radiation detector and x-ray CT apparatus
JP2008024739A
Co-doping method for modifying scintillation and optical properties of garnet-type scintillators
JP2016506977A
Method for shortening scintillation response of luminescent center and scintillator material with shortened scintillation response
JP2018536153A
Fluorescent material and method for preparation thereof, radiation detector using fluorescent material, and x-ray ct device
WO2006068130A1